The dental record: Importance as a legal document and a safeguard against litigation (Research, Society and Development, 2025)
This article aims to understand the legal relevance of dental records as essential documents and means of evidence for the defense and protection of dentists in ethical, administrative, and judicial proceedings. The present review seeks to provide references regarding the importance of dental records as legal documents. Twenty articles published between 2016 and 2025 were selected from the SciELO (Scientific Electronic Library Online), PubMed, LILACS, CAPES Journals, Google Scholar, and Virtual Health Library databases, using the following descriptors: “Medical Records”; “Dental Legislation”; “Documentation” and “Forensic Dentistry”. Results: We selected 20 scientific articles focused on the importance of dental records, classified as follows: literature review (8), integrative review (3), descriptive cross-sectional research (4), review article (1), field research (1), analytical quantitative research (1), experience report (1), and qualitative study (1).